Effect of Digital Cryptocurrency Model Bitcoin Regulation on Payment Systems in MSMEs (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2020)
Online payment transactions not only use a nominal amount of money, but also use an alternative payment method using virtual money or known as bitcoin. The research objective is to analyze and determine the effect of digital cryptocurrency regulations on the payment system for Micro, Small and Medium Enterprises (MSMEs), to find out how many MSMEs have used bitcoin, the extent of the development of bitcoin. This research uses qualitative methods with primary data obtained from distributing questionnaires and secondary data related to research through books, journals, data from the Ministry of Finance and Bank Indonesia. The research was conducted in Banyumas Regency using a sample of 250 respondents consisting of the MSMEs and non MSMEs virtual currency users. The sample selection was done through non-probability sampling method, namely purposive sampling method and the data were analyzed using multiple linear regression analysis with SPSS application tools. The variables used in this study are Bank Indonesia regulations, system security, and financial service authority regulations as variable X while variable Y is the payment system for MSMEs. The results of the analysis of each regression coefficient are b1 = -0.021; b2 = 0.043; b3 = 0.10. The conclusion of the study is that the regulation of the use of digital cryptocurrency has a relatively small significance effect on the payment system for MSMEs in the city of Purwokerto. The use of bitcoin has increased even though there are no applicable regulations in Indonesia, especially the Banyumas area.